Cleaner production in the Americas: Management of energy resources. Case Study: Chile, Costa Rica and Nicaragua - Zúñiga-Araya, Melanny (2014)
This research highlights the importance of Energy Efficiency in the subject of Cleaner Production, identifying actions that have taken place in Nicaragua, Costa Rica and Chile. The energy situation in each country is displayed and highlighted the importance of energy efficiency, in addition to highlighting the law and institutions of this issue. Besides general data of the country context are presented, allowing understanding the global situation.